Design and Implementation of Smart Home Managemen System Based on RESTful Web Services - Zhihua Li; Quanqi Gu; Jianfei Tang; Liang Xue; Jijun Zhao (Dianxin kexue)
Current smart home system based on internet of things only provides a solution to interconnect different appliances inheterogeneous networks. It still faces a lot of challenges, such as single management platform, poor scalability, and low user experience. A novel smart home management system was demonstrated, which based on a home wireless network using ZigBee technology. More importantly, the RESTful Web Services was also imported to enhance the scalability and cross-platform capability of the system. In addition, an app based on Android platform was developed for users to enhance the user experience ofmanaging smart home.